None of the above: non-religious identity in the US and Canada - Thiessen, Joel (Secular studies, 2020)
Introduction: Religious nones in the United States and Canada -- I'm done . . . and I'm not going back! -- Nones of all shapes and sizes -- We are just as moral . . . if not more! -- I want everybody to have the same chance to find happiness -- It's too bad your parents aren't Christian . . . -- Conclusion: Darlene, Patrick, Corrine, and Sandra.